Bridging the gap : journalists’ role orientation and role performance on Twitter - Tandoc, Edson C., Jr. (2020)
Combining a content analysis of 760 tweets and a survey of journalists who tweeted them, this study revisits the questioned assumption that journalists’ conception of their roles manifests in their journalistic outputs. Studies that have tested this assumption instead found a gap between role orientation and performance, possibly explained by how journalistic outputs are organizational products. Thus, this study focused on role performance as observed in journalists’ individual posts on Twitter, a social media platform that has been normalized and now embedded in news routines. If tweets are personal outputs, they should bear the imprint of the journalists who posted them. The findings of this study lend support to this claim.